Canaíma no contexto dos romances sobre a selva / Canaíma in the context of the novels about the jungle - Miyazaki, Tieko Yamaguchi (Revista de Letras, 2007)
No presente artigo, em continuação a outros trabalhos já publicados, a autora procura localizar o romance Canaíma de Rômulo Gallegos no contexto das obras latino-americanas que abordam o tema da selva. Através de alguns componentes – temáticos e estruturais – comuns a elas, mostra as diferenças que situam o romance venezuelano em um ponto ficcional que vai desde Rivera a Carperntier In this paper, in continuation of previously published articles, the authors attempts to situate the novel canaima by romulo Gallegos in the context of the Latim American works which tacks the theme of the jungle. Through some thematic and structural components common to them, she shows the differences which place the Venezuelan novel in an intermediate point in the fictional trajectory which goes from Rivera to Carpentier.